ANALISIS TINGKAT PENDAPATAN PADA UMKM - Mardiah, Ainil; Lamsir, Seno; Amalia, Amalia; Prihanto, Purwaka Hari; Mahmudin, Tono (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the income level of MSMEs that depends on capital, length of business, education, and technology. This study uses a quantitative method with direct data collection from primary sources. The sample in this study was 20 MSMEs. The data collection technique used in this study was a questionnaire. Data analysis used multiple linear regression and processed using SPSS. The results of this study indicate that partially capital, length of business, and technology have a significant effect on the income level of MSMEs. Meanwhile, partially education does not have a significant effect on MSME income. Simultaneously, capital, length of business, education, and technology together influence the income level of MSMEs.